Developing comprehensive perinatal quality of care instruments in Mexico: An inclusive, multidisciplinary, and culturally sensitive approach - Jimena Fritz; Pablo Montero-Zamora; Cara B. Safon; Pablo Martínez-Garrido; Matthias Sachse-Aguilera; Hernán García; Paola Sesia; Raffaela Schiavon; Héctor Lamadrid-Figueroa (PLoS ONE, 2026)
Ensuring high-quality care during pregnancy, childbirth, postpartum, and the newborn period is essential for reducing maternal and neonatal morbidity and mortality. In Mexico, a significant gap exists in comprehensive, culturally relevant instruments to assess quality of care (QoC) across these critical stages. This study aimed to develop robust, context-specific instruments to evaluate key dimensions of maternal and neonatal care, including patient experience, clinical processes, and hospital infrastructure. Using a modified Delphi method, we conducted two national workshops with 78 unique national experts, including academic researchers, healthcare decision-makers, and maternal health advocates. In Workshop 1, 45 experts identified 1,162 QoC indicators, which our research team subsequently reduced to 521 through a systematization process. Workshop 2 engaged 62 experts–approximately 20% of whom had also participated in Workshop 1–who discussed and rated the 521 indicators. Based on these expert ratings, our research team conducted a subsequent systematization, which further reduced the list to 489 QoC indicators. The final 489 indicators were categorized into five core QoC domains (i.e., Woman, Care Processes, Health Personnel, Infrastructure, and Supplies and Medications ) and used to develop three instruments (1) a Semi-Structured Interview Guide to explore women’s care experiences; (2) a Childbirth Observation Instrument to assess QoC during labor and immediate postpartum care, including sociodemographic details, facility characteristics, clinical processes, and adherence to best practices, and (3) a Hospital Information Instrument to gather data on infrastructure, personnel, supplies, medications, and service utilization. These instruments offer a rigorous, context-specific framework for evaluating maternal and neonatal QoC in Mexico, helping identify gaps, guide improvements, and promote health equity. They address a critical need by providing tailored tools with strong potential to inform practice and improve outcomes.